Perencanaan Instalasi Pengolahan Air Limbah Rumah Sakit dr. Achmad Diponegoro Putussibau Kabupaten Kapuas Hulu - Hardiyantiningsih, Vitranda Wenny; Winardi, Winardi; Fitrianingsih, Yulisa (Universitas Tanjungpura, 2024)
Liquid waste from hospitals is one of the by-products of various activities. This liquid waste contains many hazardous pollutants that pose a danger to hospital occupants, workers, visitors, and the surrounding community. The objectives of the planning for the wastewater treatment plant at RSUD dr. Achmad Diponegoro include designing the IPAL tank, determining the treatment method, calculating the required area in the planning process, and estimating the budget. The results of the design of the wastewater treatment facility at RSUD dr. Achmad Diponegoro use a total water demand of 78 m3/day as the basis for calculations. The wastewater treatment planning at RSUD dr. Achmad Diponegoro Putussibau uses the activated sludge treatment method, supplemented with other tanks to ensure a continuous process. The designed structure consists of seven tank, including a bar screen with an area of 0,200 m2, a collection tank with an area of 0,85 m2, an equalization tank with an area of 2,62 m2, an activated sludge tank with an area of 8,2 m2, a sedimentation tank with an area of 1,60 m2, a disinfection tank with an area of 2,13 m3, and a sludge drying bed with an area of 3 m2. The land area required for the construction of the wastewater treatment plant at RSUD dr. Achmad Diponegoro is 18,6 m2. The total estimated budget for the entire project is approximately IDR 906,500,000.00.